Potential application of biomass derived graphene for COVID-19 pandemic - Arifin, N.F.T. (Elsevier Ltd, 2020)
Since the emergence of the novel coronavirus disease (COVID-19) pandemic, intense research has been carried out to find the effective vaccine. However, this issue remains as a global challenge. Graphene has captured various attention due to promising antimicrobial and antiviral applications, hydrophobic characteristic and superior electrical conductivity. Recently, biomass derived graphene also promises great opportunity to combat the spread COVID-19. In this paper, we demonstrated the ability and role of biomass derived graphene as superhydrophobic coating, biosensors and disinfectant in the fight against COVID-19. Â© 2020 Elsevier Ltd. All rights reserved.